Reluctant disciplinarian : advice on classroom management from a softy who became (eventually) a successful teacher - Rubinstein, Gary. (Fort Collins, CO : Cottonwood Press, 1999)
The author presents practical advice for teachers on student discipline, relating mistakes he made in his first few years and explaining how he remedied them.
Professional
Keywords: Classroom management -- United States; Rewards and punishments in education; School discipline; Teacher-student relationships -- United States; Classroom management; Rewards and punishments in education; School discipline; Teacher-student relationship